2012
DOI: 10.1111/j.1651-2227.2012.02690.x
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin and symmetric dimethylarginine plasma levels in solitary functioning kidney in children

Abstract: Aim:  The present study aimed to examine whether plasma osteopontin (pOPN) and symmetric dimethylarginine (pSDMA) are useful biomarkers of renal dysfunction in children with solitary functioning kidney (SFK). Methods:  We measured circulating pOPN and pSDMA in 51 patients with SFK and no other urinary defects. Patients were subdivided into two groups: primary SFK (pSFK) – unilateral renal agenesis (URA), and secondary SFK (sSFK) – unilateral nephrectomy. The control group (C) contained 21 healthy children, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Similarly, Taranta-Janusz and colleagues [45] , reported increased plasma osteopontin and SDMA levels in children with solitary functioning kidney and both plasma osteopontin and SDMA levels were correlated with eGFR. Recently, Protas et al.…”
Section: Discussionmentioning
confidence: 81%
“…Similarly, Taranta-Janusz and colleagues [45] , reported increased plasma osteopontin and SDMA levels in children with solitary functioning kidney and both plasma osteopontin and SDMA levels were correlated with eGFR. Recently, Protas et al.…”
Section: Discussionmentioning
confidence: 81%
“…After an initiative by the International Federation of Clinical Chemistry, a uniform calibrator for cystatin C has been developed, which will probably improve the implementation of cystatin C as a marker for pediatric CKD (38). In this light, it would also be interesting to compare cystatin C with novel markers for CKD in patients with an SFK, such as fibroblast growth factor 23, osteopontin, and symmetric dimethylarginine (39,40).…”
Section: Discussionmentioning
confidence: 99%
“… Brooks et al (2008) observed reduced plasma arginine and elevated ADMA and SDMA in pediatric/adolescent CKD (stage 2–3) patients, with SDMA demonstrated to be a strong indicator of reduced GFR. Importantly, in a small cohort of 51 children with a SFK at a mean age of ∼10 years, plasma SDMA was significantly elevated and negatively correlated with GFR, suggesting that plasma SDMA may serve as a marker of endothelial dysfunction in children with a SFK ( Taranta-Janusz et al, 2012 ).…”
Section: Biomarkers and Areas Of Future Studymentioning
confidence: 99%